Methodology and technology for peripheral and central blood pressure and blood pressure variability measurement: current status and future directions – Position statement of the European Society of Hypertension Working Group on blood pressure monitoring and cardiovascular variability. Issue 9 (September 2016) - Stergiou, George S.; Parati, Gianfranco; Vlachopoulos, Charalambos; Achimastos, Apostolos; Andreadis, Emanouel; Asmar, Roland; Avolio, Alberto; Benetos, Athanase; Bilo, Grzegorz; Boubouchairopoulou, Nadia; Boutouyrie, Pierre; Castiglioni, Paolo; et al.
Abstract : Office blood pressure measurement has been the basis for hypertension evaluation for almost a century. However, the evaluation of blood pressure out of the office using ambulatory or self-home monitoring is now strongly recommended for the accurate diagnosis in many, if not all, cases with suspected hypertension. Moreover, there is evidence that the variability of blood pressure might offer prognostic information that is independent of the average blood pressure level. Recently, advancement in technology has provided noninvasive evaluation of central (aortic) blood pressure, which might have attributes that are additive to the conventional brachial blood pressure measurement. This position statement, developed by international experts, deals with key research and practical issues in regard to peripheral blood pressure measurement (office, home, and ambulatory), blood pressure variability, and central blood pressure measurement. The objective is to present current achievements, identify gaps in knowledge and issues concerning clinical application, and present relevant research questions and directions to investigators and manufacturers for future research and development (primary goal).